Characterization and Topical Study of Aloe Vera Hydrogel on Wound-Healing Process - Saucedo Acuña, Rosa Alicia (2021)
Wound healing is fundamental to restore the tissue integrity. A topical study of the influence of Aloe vera hydrogel, formulated with 1,2-propanediol (propanediol) and triethanolamine (TEA), on the skin wound-healing process was investigated in female Wistar rats. FTIR spectroscopy confirms the presence of carboxylic acid and methyl ester carboxylate groups related with important compounds that confer the hydrogel a good interaction with proteins and growth factors. SEM images show a microstructure and micro-roughness that promote a good adhesion to the wound. Therefore, the swelling kinetics and the contact angle response contribute to the understanding of the in vivo results of the animal test. The results indicated that the Aloe vera hydrogel, prepared with propanediol and TEA, together with its superficial characteristics, improve its rapid penetration without drying out the treated tissue. This produced a positive influence on inflammation, angiogenesis, and wound contraction, reducing 29% the total healing time, reaching the total closure of the wound in 15 days.